Validação do questionário skindex-29 - Carvalho, Daniela (2018)
Introduction: There is an increasing interest regarding the impact of skin diseases on quality of life. Skindex-29 is a questionnaire developed to evaluate this impact. This study aimed to validate Skindex-29 for the Portuguese population. Material and Methods: From the 81 approached patients from two clinics, only 75 finished the study: 35 with skin disease and 40 without. A translation and back-translation were performed. Concerning accuracy and discrimination power, the scores were submitted to ROC curve analysis after being compared between both groups through Mann-Whitney test. Internal consistency was measured using Cronbach’s α coefficient. Test/retest of each scale was assessed by the intra-class correlation coefficient, and by Kappa coefficient of agreement. Convergent validity was evaluated through Spearman correlations between Skindex-29 scores and SF-12 subscales. SPSS statistics and values of p < 0.05 with 95% confidence intervals were considered statistically significant. Results: The Skindex-29 demonstrated to be an accurate instrument and statistically significant differences were found when comparing the disease and without-disease groups (p < 0.001). The reliability was high (Cronbach’s α > 0.80) for each dimension (‘Symptoms’, ‘Emotions’ and ‘Functioning’) and for test-retest (ICC > 0.90, K > 0.494). About convergent validity, Skindex-29 Total score and the questions about ‘Symptoms’ and ‘Functioning’ were statistically correlated with the questions regarding the physical state of the SF-12 (-0.478;-0.459;-0.405, respectively). Discussion: Results suggest that Skindex-29 can be used as an instrument to evaluate skin diseases’ effect on quality of life in Portugal, being accurate and reliable. Despite having similar general health profiles as other individuals, dermatological patients showed a lower quality of life due to their disease. Results showed that Skindex-29 was better at assessing physical components rather than mental or emotional components. Conclusion: Skindex-29 appears to have evidence of validity including accuracy and reliability to be used as an instrument to evaluate the impact of skin diseases on quality of life in Portugal.